Assessment of Bali cattle semen using different collection methods, ulatrastructural changes of spermatozoa, and relationship between seminal plasma proteins andin vitro fertility - Sarsaifi, Kajal (2013)
Male infertility is a major issue in mammalian reproduction and thus, it is important to ascertain that a bull is fertile prior to breeding. The potential fertility of a bull can be determined by field fertility rates. However, this procedure of determining fertility is expensive and time-consuming. Therefore,the present study was designed to develop a method for the prediction of frozenthawed Bali cattle spermatozoa fertility using various sperm characteristics and heterologous in vitro fertilization (IVF) of zona-free hamster oocytes (ZFHOs). The main objective of the study was to evaluate the protein composition of the seminal plasma of Bali bulls and the proteins related to bull fertility. Semen samples were collected from 25 untrained Bali bulls using three different collection methods namely electrical ejaculation (EE), rectal massage (RM) and a combination of RM and EE. The effects of these methods on pre- and pos thawed semen characteristics were evaluated. All specimens were assessed for motility characteristics, capacitation, acrosome and membrane integrities,acrosome reaction, and ultrastructure. To assess the fertility of frozen-thawed bull spermatozoa, heterologous IVF using ZFHOs was conducted. To improve sperm penetration into ZFHOs, three sperm separation methods namely Swimup,Percoll® and BoviPure®, were used. Prior to co-incubation with ZFHOs, the spermatozoa were first incubated in four media containing 0, 25, 50 and 100 μg/ml heparin. The relationship between different motions of sperm characteristics semen assessed by CASA and the percentage of IVF success were also studied. In another study, the seminal plasma proteins (SPP) were separated using 2-dimensional SDS-PAGE followed by Coomassie blue staining and the polypeptide maps were analyzed using the Image Master Software. Proteins were identified by Matrix-assisted laser desorption/ionization time-offlight mass spectrometry (MALDI-TOF-MS/MS). The results of the study showed that EE and combination method (RM-EE) can be used to obtain semen from Bali cattle, with a 100% success rate with the EE method. Post-thawed semen collected using the EE method was also of acceptable quality that would increase the chance of conception, and subsequently can be used in the conservation of Bali cattle. Better fertilization percentages (FP) and fertilization indexes (FI) were observed in ZFHOs inseminated with spermatozoa separated by Swim-up and BoviPure® compared to the Percoll® method. In addition the higher heparin concentrations (50 and 100 μg/ml) with 30 min incubation time improved heterologous IVF rates (FP: 68.42-74.64 % and FI: 3.15-3.73). With regards to FP and FI, significant differences (P<0.05) were observed between bulls from heterologous IVFs of ZFHOs with Swim-up spermatozoa and BoviPure® spermatozoa group. Among the spermatological and IVF parameters, FP (r2= 0.930) and FI (r2= 0.875) were identified as being the most predictive of bull fertility and have high correlations with acrosome reaction (r2=0.830). The results suggest that heterogeneous IVF using ZFHOs is potentially an informative method for assessing in vivo fertilization ability of Bali bulls. Bulls of high fertility had significantly higher mean values of sperm characteristics compared to infertile bulls. Statistical analysis of percentage motility, morphology and FP showed that the correlation coefficient between sperm qualitative characteristics and overall bull fertility were significant (P<0.05). Based on these findings, the proteomics profiling of seminal plasma of Bali bulls have significant merit. An average of 116 ± 8 spots was detected on the SPP gels. An interesting finding in this study is that there were three spots,namely 9, 13 and 16 (MW: 14 to 16 kDa, and PI: 4.9 to 5.8), which were generally more significantly intense in the infertile group than in the fertile group. Upon MALDI-TOF-MS/MS analysis, these three spots were identified as a type of bovine SPP (PBSA1/A2) known as PDC-109 that was up-regulated (P<0.05) in the infertile Bali cattle group. The PDC-109 is involved in sperm capacitation and fertilization and its abundance is associated with fertility of Bali bulls. Spots 3 and 5, identified as sperm-adhesion proteins (MW: 13 to 15 kDa and PI: 5 to 5.8) were not significant (P>0.05) up-regulated in the infertile group. Spots 18 and 68, known as seminal ribonuclease (MW; 14 to 16 kDa and PI; 8.4 to 9.3), were significantly down-regulated (P<0.05) in the infertile group. However, spot 68 was found at the edge of the acidic site, so it may not serve as a good potential marker due to the limitation of pI range (3 to 10) in the ReadyStrip™. Spot 79, which is serum albumin, was also down-regulated in the infertile group. This is the first report on the PDC-109 abundance related to bull fertility. This study is also a first comprehensive description of Bali cattle semen and seminal plasma proteome. These findings suggest that there are several proteins in the Bali cattle seminal plasma fluid which could be related to the fertility of this species.